(untitled) (ACME, 2022)
Among the marble furnishings of the Roman age, a group of supports made of Giallo antico marble stands out. The specimens, with common characteristics of workmanship and decoration, were found in the western Mediterranean (Sardinia, southern France, Spain), with a concentration in some ancient centers. Considerations are proposed on the production, circulation and reuse of these luxury items.